Antifungal activity of neem leaf ethanol extract on Aspergillus flavus - Ayly Margaret; Hanna Yolanda; Wibisono Lies K (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUNDAspergillosis is an infectious disease due to inhalation of Aspergillus spores.Drug resistance to aspergillosis has been reported since 14 years ago. Therefore,alternative treatment using herbals began to attract the attention of the medicalprofession and the community, because herbals are relatively safe and haveminimal side effects. Neem (Azadirachta indica) is an herb with broad spectrumbiological activity, but studies on the antifungal activity of neem leaves arelacking. The objective of this study was to evaluate the activity of neem leaveson Aspergillus flavus (A. flavus).METHODSThis was a laboratory experimental study using A. flavus samples obtained frombronchial washing specimens of inpatients. Neem leaf extract in ethanol (NLE)was prepared in various concentrations. Aspergillus. flavus antifungal activityof NLE were assessed by disc diffusion (using NLE at 1.0; 0.75; 0.50; 0.25 g/dL)and macrodilution (using NLE at 1.0; 0.75; 0.5; 0.25; 0.125 g/dL). Ketoconazole0.1 g/dL was used as antifungal positive control. Disc diffusion and macrodilutionwere conducted using Sabouraud dextrose agar and broth, to measure inhibitionzone diameter and minimal inhibitory concentration (MIC), respectively. Statisticalanalysis was performed using Mann-Whitney test from SPSS 15.RESULTSThere were significant differences in inhibition zone diameter (p = 0.034) betweenA. flavus samples exposed to NLE (1 g/dL) and the control group exposed toketoconazole (0.1 g/dL). The MIC of NLE against A. flavus was 0.5 g/dL.CONCLUSIONSNeem leaf ethanol extract has antifungal activity against A.flavus in vitro.